2022
DOI: 10.1111/acps.13505
|View full text |Cite
|
Sign up to set email alerts
|

Delirium‐associated medication in people at risk: A systematic update review, meta‐analyses, and GRADE‐profiles

Abstract: Background: Drug-associated delirium is a common but potentially preventable neuropsychiatric syndrome associated with detrimental outcomes. Empirical evidence for delirium-associated medication is uncertain due to a lack of highquality studies. We aimed to further investigate the body of evidence for drugs suspected to trigger delirium.Methods: A systematic update review and meta-analyses of prospective studies presenting drug associations with incident delirium in adult study populations was conducted. Two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(394 reference statements)
0
1
0
Order By: Relevance
“…The absolute difference between the cumulative prescribing of anticholinergic drugs and of general medications without putative anticholinergic effects was 0.03 to 0.05 (OR), depending on the outcome. If the effect of polypharmacy, instead of a null effect, is considered the reference value, the effect of anticholinergic use is thus much smaller than what was previously reported in studies that did not control for polypharmacy in this way 1,3,[28][29][30] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The absolute difference between the cumulative prescribing of anticholinergic drugs and of general medications without putative anticholinergic effects was 0.03 to 0.05 (OR), depending on the outcome. If the effect of polypharmacy, instead of a null effect, is considered the reference value, the effect of anticholinergic use is thus much smaller than what was previously reported in studies that did not control for polypharmacy in this way 1,3,[28][29][30] .…”
Section: Discussionmentioning
confidence: 91%
“…The sum of an individual's values yields a weighted burden score -the anticholinergic burden -that can be used by clinicians or researchers to identify patients or populations vulnerable to adverse side effects. Anticholinergic burden has been associated with adverse long-term health outcomes, including all-cause mortality 1 , dementia 2 , and delirium 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials that used perioperative ketamine to prevent POD and neurocognitive impairment showed that ketamine did not significantly affect the incidence of POD compared with a placebo (Hovaguimian et al, 2018;Souad et al, 2023;Viderman et al, 2023). But to be clear, ketamine did not increase the risk of POD (Reisinger et al, 2023). The negative results of these prior clinical trials are in stark contrast to the relatively solid theoretical support for the efficacy of ketamine in the prevention of POD.…”
Section: Clinical Evidence and Pharmacological Deficiencies Of Ketami...mentioning
confidence: 99%